2021
DOI: 10.3389/fgene.2021.755486
|View full text |Cite
|
Sign up to set email alerts
|

A Ferroptosis-Related Gene Signature for Predicting the Prognosis and Drug Sensitivity of Head and Neck Squamous Cell Carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) is one of the most common cancers worldwide and has a high mortality. Ferroptosis, an iron-dependent form of programmed cell death, plays a crucial role in tumor suppression and chemotherapy resistance in cancer. However, the prognostic and clinical values of ferroptosis-related genes (FRGs) in HNSCC remain to be further explored. In the current study, we constructed a ferroptosis-related prognostic model based on the Cancer Genome Atlas database and then explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Ferroptosis is morphologically, biochemically, and genetically distinct from other cell deaths, suggesting its therapeutic potential for HNSCC. Recently, sequence-based studies have shown that ferroptosis-related gene signature plays an important role in the development and treatment of HNSCC [ 18 20 ]. CAV1, which could inhibit ferroptosis, leads to cancer progression in HSNCC [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ferroptosis is morphologically, biochemically, and genetically distinct from other cell deaths, suggesting its therapeutic potential for HNSCC. Recently, sequence-based studies have shown that ferroptosis-related gene signature plays an important role in the development and treatment of HNSCC [ 18 20 ]. CAV1, which could inhibit ferroptosis, leads to cancer progression in HSNCC [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…BNIP3 is regarded as a proapoptotic protein, whose dysregulated expression is related to mitophagy, autophagy, and pyroptosis [67][68][69]. Tumor cells are sensitive to cisplatin and gemcitabine when BNIP3 upregulates [70]. Interestingly, the expression level of BNIP3 will elevate in early-stage adenocarcinoma but decrease in metastasis progression.…”
Section: Discussionmentioning
confidence: 99%
“…The ROC curve and decision curve analysis (DCA) were also used to assess the precision of the model compared to the traditional clinical features. The comparison between the established models was utilized to assess the forecasting ability of the novel model [ 16 , 24 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…e comparison between the established models was utilized to assess the forecasting ability of the novel model [16,[24][25][26][27][28].…”
Section: Establishment Of the Risk Modelmentioning
confidence: 99%